PENINGKATAN SDM BERBASIS EKONOMI KREATIF MELALUI OLAHAN PEPAYA MUDA - Maryana, Maryana; Shalawati, Shalawati; Maisyuri, Maisyuri; Alfahmi, M. Lutfi; Keumala, Cut Muftia; Fazilah, Nura; Ramadhanty, Helsy (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Creative economy is a concept in the new economic era that intensifies information and creativity by relying on ideas and knowledge from human resources as the main production factors. The secret of the creative economy lies in creativity and innovation. The creative economy emphasizes the power of ideas and concepts that are based on the strength of human resources aspects. Optimizing the capacity of human resource empowerment in the village is done by providing socialization and training to process the potential that exists around the community and providing reinforcement to the community in the village. Gampong Jawa Baru is located in the coastal area of Lhokseumawe City and papaya plants are often found and planted by the residents on their yards. However, the use of papaya among the community was still less than optimal due to the lack of knowledge, ideas and creativity from the community. Therefore, it was considered necessary to conduct training related to the processing of papaya fruit, one of which is in the form of processed papaya sticks. The method of implementing the activity was carried out through the delivery of materials, discussions, and product making practices. The results of the implementation of this community service activity showed an increase in the knowledge and creativity of the community in utilizing local food, specifically papaya fruit, and the participants were very enthusiastic and even the community expected further training on product packaging and marketing.